دور الاستخبارات التسويقية في خلق اليقظة التنافسية دراسة مقارنة بين فروع المصرف التجاري وفروع بنك بيمو في الساحل السوري (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aims to study the role of marketing intelligence in creating competitive vigilance at the branches of the commercial bank and branches of Bemo Bank operating in the Syrian coast.. The researcher used the descriptive approach and developed a questionnaire to collect preliminary data about research sample’s vocabularies, which was a simple consists of Staff (head of department / manager) was on the Syrian coast.  The questionnaire was distributed to the staff of the banks in the study, where they reached 79 employees, but only 66 of them were valid questionnaires. The questionnaire used a Likert Scale )five points scale). Furthermore, the analysis used statistical indicators that were appropriate for nominal and grade data. Finally, reliability and validity of honesty testing was conducted to determine the suitability of questionnaire’s questions to the research goal, as well as a set of testing differences between averages. The research concluded the following findings: 1.There is statistically significant relationship between marketing intelligence and its ability to achieve competitive vigilance at organizations. 2.There is a correlation significant relationship between competitor’s position and attitude study and achieving competitive vigilance. 3.There is a correlation significant relationship between customers’ study and achieving competitive vigilance. يهدف البحث إلى دراسة دور الاستخبارات التسويقية في خلق اليقظة التنافسية عند فروع المصرف التجاري وفروع بنك بيمو العاملة في السّاحل السّوري. اعتمدت الباحثة على المنهج الوصفي، وقامت بتطوير استبانة لجمع البيانات الأوّليّة عن مفردات عيّنة البحث، وكانت عيّنة ميّسرة من الموظفين (رئيس قسم/ مدير) في السّاحل السوري. ووزعت الاستبانة على موظّفي البنوك محل الدّراسة حيث بلغ عددهم 79 موظفا ، حيث تم استرجاع 66 استبانة صالحة للتحليل، واستخدم في استبانة البحث مقياس ليكرت خماسي الاتجاه، كما استخدمت في التحليل المؤشرات الإحصائية الملائمة لطبيعة البيانات الاسمية والرتبية، وتمّ تطبيق اختبار مستوى الصدق والثبات لتحديد مدى ملائمة أسئلة الاستبيان لهدف البحث، إضافة إلى مجموعة من اختبارات الفروق بين المتوسطات. توصلت الدراسة الى مجموعة من النتائج أهمها: 1-                توجد علاقة ذات دلالة إحصائية بين الاستخبارات التسويقية وقدرتها على تحقيق اليقظة التنافسية للمنظمات. 2-                توجد علاقة ذات دلالة معنوية بين دراسة موقع ومكانة المنافس وبين تحقيق اليقظة التنافسية. 3-                توجد علاقة ذات دلالة معنوية بين دراسة المستهلكين وبين تحقيق اليقظة التنافسية.